High-power broad-area buried-mesa lasers. (15th May 2017) - Della Casa, P; Brox, O; Decker, J; Winterfeldt, M; Crump, P; Wenzel, H; Weyers, M
Abstract: Broad area lasers emitting near 940 nm are fabricated using a process based on two-step epitaxy. The n-side of the layer structure and the active layer are grown during the first epitaxial step, the p-side during the second. Between the first and the second step a shallow etching is used to remove the active layer from the two sides and at the two facets. This simple approach allows the creation of buried mesa lasers with non-absorbing mirrors, resulting in a reduced lateral current leakage, lower threshold current and higher efficiency, plus an increased robustness with respect to catastrophic optical damage.